(Re)making quality in China's dairy industry. Issue 4 (2nd October 2018) - Tracy, Megan
Abstract: Quality in the food industry is viewed at once as both a standard of excellence to be reached and as an attribute, characteristic, or property to be imbued in products and people. In contemporary China, quality is further divided into suzhi or "human" quality reserved to describe embodied characteristics with a range of other terms used to describe the attributes of institutions, objects, and other non-human entities. This article explores how various ideas of quality transfer or circulate among people, places, and things. I consider the manner in which various activities—such as milking cows, producing indigenous foods, and advertising—stabilize notions of quality through their attachment to particular objects and practices. Using data collected within China's dairy industry before and after the industry's epic 2008 melamine adulteration scandal, I revisit the notion of human quality and examine it in dialogue with Callon's work on the qualification of objects.